Minimum participation requirements and the role of co-benefits in international climate policy - Brumme, Anja; Rübbelke, Dirk (Frontiers in Environmental Economics, 2023)
Effective combat of international environmental problems regularly necessitates a minimum number of participating countries. Some international environmental treaties like the Paris Agreement combating global warming and the Montreal Protocol protecting the ozone layer required that a minimum participation threshold be met before they entered into force. Albeit the immense challenge to protect the global climate, the Paris Agreement additionally demands to address sustainable development and therefore seeks to take advantage of potential co-benefits of climate protection measures. This article is, to the authors' knowledge, the first to investigate in 3 × 3 normal form games the prospects for effective international cooperation on climate protection if effectiveness requires a minimum number of participating countries. The main findings are, first, that sustainable development co-benefits from mitigation might increase the chance that the minimum participation threshold is met and climate policy will be effective in the end; and second, if domestic ancillary benefits from mitigation are rather small, new organizational designs could create additional sustainability benefits that are limited to mitigating countries. For example, a win-win situation – regarding climate and sustainability – could be achieved by international policy designs that create additional co-benefit spillovers via the establishment of a club pursuing sustainable innovations (in line with UN Sustainable Development Goal 9).